The Influence of Opioid Use Disorder on Open Reduction and Internal Fixation following Ankle Fracture - Megan K. Allen MPH; James M. Parrish; Rushabh M. Vakharia MD; Jonathan R. Kaplan MD; Ettore Vulcano MD; Martin W. Roche MD; Amiethab A. Aiyer MD (Foot & Ankle Orthopaedics, 2020)
Category: Ankle; Other Introduction/Purpose: Ankle fractures are common injuries that may require surgical treatment consisting of open reduction and internal fixation (ORIF). Injuries associated with increased pain levels are also correlated with increased opioid use, which is also recognized as a risk factor for bone fracture. There is a paucity of literature evaluating the impact of patients with a history of opioid use disorder (OUD) on postoperative complications following ORIF for ankle fracture. This study aims to investigate whether OUD patients are at greater odds of: 1) readmission rates, 2) emergency room visits, and 3) costs of care. Methods: Patients undergoing ORIF for ankle fracture with a 90-day history of OUD prior to the procedure were identified using national health insurance claims database. We selected patients that underwent surgical corrections as recorded by the following current procedural terminology (CPT) medical codes: 27792, 27814, 27822, 27823, 27766, 27829, and 27769. We matched cases with OUD to controls with a 1:4 of OUD to non-OUD controls. Variables that were matched between non-controls and controls included age, sex, Elixhauser- Comorbidity Index (ECI), in addition to comorbidities including diabetes, hyperlipidemia, hypertension, and tobacco usage. Logistic regression analysis was used to calculate odds-ratios (OR) for outcomes of 90-day readmission rates and emergency room visits. Welch’s t-test was used to test for significance of outcomes of cost of care and ECI between the cohorts. A p-value less than 0.001 was statistically significant. Results: A total of 2,198 patients were included with (n= 485) and without (n = 1,698) OUD undergoing ORIF for ankle fracture (Table 1). OUD patients undergoing ORIF for ankle fractures were found to have a higher incidence and odds of 90-day readmission rates compared to controls (8.65 vs. 7.30%; OR: 1.20, 95%CI: 0.83 - 1.73, p=0.320), but failed to reach statistical significance. OUD patients were found to have a higher incidence and odds of emergency room visits compared to controls (3.50 vs. 0.64%; OR: 5.57, 95% CI: 2.59 - 11.97, p<0.0001). OUD patients also incurred significantly higher costs of care compared to controls ($5,921.59 vs. $5,128.22, p<0.0001). Conclusion: Patients with OUD have greater odds of 90-day hospital readmission rates, emergency room visits, and costs of care following ORIF procedures for ankle fracture. These outcomes are consistent with previous research which found increased costs associated with individuals diagnosed with OUD prior to undergoing other foot and ankle procedures. This study, establishes that patients with OUD place a significant, but preventable, financial burden on healthcare resources. The findings of this study highlight the role that foot and ankle orthopaedic surgeons can play in reducing healthcare costs and improving patient outcomes by addressing OUD prior to the occurrence of injury.